FINITE ELEMENT MODELING OF CIRCULAR REINFORCED CONCRETE COLUMN CONFINED WITH CFRP UNDER ECCENTRIC LOADING - Angga Bayu Christianto; Bambang Piscesa; Faimun Faimun; Pujo Aji (Journal of Civil Engineering, 2019)
This paper presents nonlinear finite element analysis of eccentrically loaded circular Reinforced Concrete (RC) column confined with Carbon Fiber Reinforced Polymer (CFRP) wraps. The concrete constitutive model uses a plasticity-fracture model which is restraint sensitive, utilize a non-constant plastic dilation rate, and is able to simulate the plastic volumetric compaction of concrete core under high confining pressure. For validation of the models, two available specimens from the literature are used in the validations. Excellent agreement between the numerical models and the available test results are obtained in this study. A detailed investigation on the confinement effectiveness of both external and internal confining devices are presented and discussed. This discussion of the confinement effectiveness is important to be included in the design formula.